Starvation Improves Survival of Bacteria Introduced into Activated Sludge - Watanabe, Kazuya (American Society for Microbiology, 2000)
A phenol-degrading bacterium, Ralstonia eutropha E2, was grown in Luria-Bertani (LB) medium or in an inorganic medium (called MP) supplemented with phenol and harvested at the late-exponential-growth phase. Phenol-acclimated activated sludge was inoculated with the E2 cells immediately after harvest or after starvation in MP for 2 or 7 days. The densities of the E2 populations in the activated sludge were then monitored by quantitative PCR. The E2 cells grown on phenol and starved for 2 days (P-2 cells) survived in the activated sludge better than those treated differently: the population density of the P-2 cells 7 days after their inoculation was 50 to 100 times higher than the population density of E2 cells without starvation or that with 7-day starvation. LB medium-grown cells either starved or nonstarved were rapidly eliminated from the sludge. The P-2 cells showed a high cell surface hydrophobicity and retained metabolic activities. Cells otherwise prepared did not have one of these two features. From these observations, it is assumed that hydrophobic cell surface and metabolic activities higher than certain levels were required for the inoculated bacteria to survive in the activated sludge. Reverse transcriptase PCR analyses showed that the P-2 cells initiated the expression of phenol hydroxylase within 1 day of their inoculation into the sludge. These results suggest the utility of a short starvation treatment for improving the efficacy of bioaugumentation.